Risiko Kecurangan Laporan Keuangan Pemerintah Pada Masa Pandemi Covid-19 - Thadeus Fransesco Quelmo Patty; Lilis Ardini (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2021)
The purpose of this paper is to find out what risks of fraud that arise during the preparation of government financial reports during the COVID-19 pandemic. This type of research used by researchers is a descriptive qualitative type. In conducting a library research (library research, literature review, literature research) a series of studies relating to the method of collecting library data, or research whose research objects are explored through various library information (books, encyclopedias, scientific journals, newspapers, magazines, and documents) . The results of the study stated that the COVID-19 pandemic posed several risks for ministries / institutions (K / L) in carrying out their duties and functions, including in preparing financial reports. There are five risks faced by Ministries / Institutions in preparing financial reports in the midst of a pandemic crisis, namely strategic, moral hazard and fraud, operational, compliance, and presentation.